GM-CSF Nitration Is a New Driver of Myeloid Suppressor Cell Activity in Tumors - Calì, Bianca; Agnellini, Andrielly H. R.; Cioccarelli, Chiara; Sanchez-Rodriguez, Ricardo; Predonzani, Andrea; Toffolo, Giulia Ilaria; Viola, Antonella; Bronte, Vincenzo; Arrigoni, Giorgio; Zonta, Francesco; Albertoni, Laura; Mescoli, Claudia; et al. (Frontiers in Immunology, 2021)
Reactive oxygen species, including RNS, contribute to the control of multiple immune cell functions within the tumor microenvironment (TME). Tumor-infiltrating myeloid cells (TIMs) represent the archetype of tolerogenic cells that actively contribute to dismantle effective immunity against cancer are among the cells most influenced by these molecules. TIMs inhibit T cell functions and promote tumor progression by several mechanisms including the amplification of the oxidative/nitrosative stress within the TME. In tumors, TIM expansion and differentiation is regulated by the granulocyte-macrophage colony-stimulating factor (GM-CSF), which is produced by cancer and immune cells. Nevertheless, the role of GM-CSF in tumors has not yet been fully elucidated. In this study, we show that GM-CSF activity is significantly affected by RNS-triggered post-translational modifications. The nitration of a single tryptophan residue in the sequence of GM-CSF nourishes the expansion of highly immunosuppressive myeloid subsets in tumor-bearing hosts. Importantly, tumors from colorectal cancer patients express higher levels of nitrated tryptophan compared to non-neoplastic tissues. Collectively, our data identify a novel and selective target that can be exploited to remodel the TME and foster protective immunity against cancer.